If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -17) + (6x + 27) = 180 Reorder the terms: (-17 + 4x) + (6x + 27) = 180 Remove parenthesis around (-17 + 4x) -17 + 4x + (6x + 27) = 180 Reorder the terms: -17 + 4x + (27 + 6x) = 180 Remove parenthesis around (27 + 6x) -17 + 4x + 27 + 6x = 180 Reorder the terms: -17 + 27 + 4x + 6x = 180 Combine like terms: -17 + 27 = 10 10 + 4x + 6x = 180 Combine like terms: 4x + 6x = 10x 10 + 10x = 180 Solving 10 + 10x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 10x = 180 + -10 Combine like terms: 10 + -10 = 0 0 + 10x = 180 + -10 10x = 180 + -10 Combine like terms: 180 + -10 = 170 10x = 170 Divide each side by '10'. x = 17 Simplifying x = 17
| xy^2-108=0 | | 3(-2)+6k-20=k(-2)-k+1 | | -4/7t=2/3 | | -(z+5)+(2z+1)=-29 | | 3(4)+6k-20=k(4)-k+1 | | 14x+15x= | | 76=2y-28 | | -2.6x=34.84 | | x-0.2x=205000 | | 2x-12/y-4 | | 2x-34=52 | | -6(x+7)-44=5-37 | | 4-2x=5x-5 | | y=-12x+36 | | -22=n/5 | | (u+7)(u+8)=0 | | 3/4*2.10 | | 7(-6-2b)=6-8b | | 20-43=4(x-1)-7 | | 0.6(6e+9f-21g)-7f= | | (-3)/(-4) | | z=13+2(x+y)forx | | 12c=156 | | 11-19c=-18c-19+c | | -14-3m=-m+10 | | -10=-9q+7 | | 10+5f=9f-10 | | 6z-1=3+4z+6 | | (9n+4)+(9n+4)=180 | | 7n+2=-2+8n | | -u=-2u-7 | | 180(n-2)=5400 |